Phylodynamics of HIV-1 subtype C epidemic in east Africa - Delatorre, Edson Oliveira (2012)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de AIDS e Imunologia Molecular. Rio de Janeiro, RJ, Brasil.